(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Dental implants have revolutionized dentistry for managing partially and fully edentulous patients. The present studywas conducted to evaluate effect of dental implant thread design on marginal bone loss using CBCT.Materials & Methods: 90 patients who received 125 dental implants of both genders were divided into 2 groups of 45 each. Group Ipatients received spiral implants and group II patients received dual fit implants. All patients were subjected to CBCT scan taken withPlanmica CBCT machine. Patients were recalled after 6 months and CBCT scans were repeated.Results: Group I had 25 males and 20 females and group II had 22 males and 23 females. The mean marginal bone loss in group I was2.01 mm and in group II was 2.23 mm. The difference was significant (P< 0.05). The mean survival rate in group I was 96.5% and ingroup II was 95.2%. The difference was significant (P< 0.05).Conclusion: Spiral implants had higher survival rate and minimum less bone loss as compared to dual fit implants. The use of CBCTcould aid in the accurate identification of bone loss around dental implants.